LITERASI DAN MINAT BACA MELALUI MODEL PEMBELAJARAN COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) BERDASARKAN GENDER DI MADRASAH IBTIDAIYAH NEGERI (MIN) 1 KOTA SAWAHLUNTO - Yasri Hosvita; Aminudin Zuhairi, Tustiyana Windiyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) model in improving students' reading literacy and reading interest based on gender at MIN 1 Sawahlunto City. This research method is a quasi-experimental with a pretest-posttest control group design. Data were collected through literacy tests and reading interest questionnaires. The results showed that students who participated in learning with the CIRC model experienced a significant increase in reading literacy and reading interest compared to students who participated in conventional learning. In addition, there were differences in literacy achievement and reading interest based on gender, where female students showed a higher increase than male students. This study suggests the widespread application of the CIRC model in elementary education as an effective strategy to improve literacy quality.